2003
DOI: 10.1016/s0042-6822(03)00125-9
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Env leader protein and the N-terminal Gag domain of feline foamy virus important for virus morphogenesis

Abstract: Previous studies have shown that foamy virus (FV) particle budding, especially the involvement of the viral env glycoprotein is different from that of other (ortho) retroviruses: the N-terminal Env leader protein Elp is a constituent of released FV particles. A defined sequence in Elp required for particle budding binds to the MA domain of Gag. To extend these findings, we show that feline FV Elp is a membrane-anchored protein with the N-terminus located inside the particle. Thus, the internal/cytoplasmic doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…As reported previously (11) and in agreement with the data presented here, FV particles contain high concentrations of the 16-kDa Elp but low levels of the 9-kDa FFV Env SP. The N-terminal sequences extending into the cytosol before budding and thereafter into the virion are identical for both proteins.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As reported previously (11) and in agreement with the data presented here, FV particles contain high concentrations of the 16-kDa Elp but low levels of the 9-kDa FFV Env SP. The N-terminal sequences extending into the cytosol before budding and thereafter into the virion are identical for both proteins.…”
Section: Discussionsupporting
confidence: 93%
“…However, for two distinct foamy retroviruses, namely human and feline foamy virus (HFV and FFV), the 14-to 18-kDa N-terminal Env cleavage product was clearly detectable as a component of released virus particles (11,14,15,35). We showed that the N terminus of FFV Env, termed the Env leader protein (Elp), is located inside particles, confirming that specific interactions between this part of Elp and Gag can occur (11,35).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The envelope (Env) proteins of the foamy viruses differ in numerous points from those of other retroviruses. They consist of the Env leader protein (Elp) [12], the surface envelope protein and the TM protein [13]. The TM proteins are larger, their central part is characterised by the presence of seven to eight cysteines and numerous potential glycosylation sites [14,15] and electron microscopic pictures demonstrate an unusual trimeric oligomerisation [16].…”
Section: Introductionmentioning
confidence: 99%